2013
DOI: 10.1371/journal.pone.0077933
|View full text |Cite
|
Sign up to set email alerts
|

Regional Homogeneity Abnormalities Affected by Depressive Symptoms in Migraine Patients without Aura: A Resting State Study

Abstract: BackgroundBidirectional relationship between migraine and depression suggests that there might be some etiological risk factors shared. However, few studies investigated resting state abnormalities affected by depressive symptoms in migraine patients without aura (MWoA).Materials and MethodsAccording to their self-rating depression scale (SDS) score, MWoA were divided into twenty in the SDS (+) (SDS > 49) group and 20 in the SDS (−) (SDS ≤ 49) group. Regional homogeneity (ReHo) method were employed to assess l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…The abnormal function of the HPA axis and other hormones can also lead to neurobiological abnormalities and structural changes in the brain [31, 42, 43]. The dysregulation of the HPA axis, changes in brain matter volume, and sensitization to high levels of stress contribute to migraine, depressive disorders, and suicidal behaviors [36, 44].…”
Section: Discussionmentioning
confidence: 99%
“…The abnormal function of the HPA axis and other hormones can also lead to neurobiological abnormalities and structural changes in the brain [31, 42, 43]. The dysregulation of the HPA axis, changes in brain matter volume, and sensitization to high levels of stress contribute to migraine, depressive disorders, and suicidal behaviors [36, 44].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, by employing resting-state functional MRI (rs-fMRI), a number of studies have demonstrated that migraine was associated with functional brain alterations measured by various indices, including the amplitude of low-frequency fluctuations (ALFF), regional homogeneity (ReHo), as well as functional connectivity. For example, compared with the healthy controls, migraineurs showed significant ALFF changes in the anterior cingulate cortex and prefrontal cortex [ 12 ], and ReHo changes in the prefrontal cortex, orbitofrontal cortex [ 13 ], insula [ 14 ], and cuneus [ 15 ]. Altered functional connectivity in migraineurs was identified between the dorsolateral prefrontal cortex and the dorsal anterior cingulate cortex [ 16 ], between amygdala and insula [ 17 ], and between the prefrontal and temporal regions that were within the default mode network [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore ReHo could be a valuable method complementary to brain structure measurement and could provide a better understanding of pathophysiological changes in brain function. Many recent studies of pain-related diseases, such as irritable bowel syndrome (IBS) [19, 28], migraine [44], and complex regional pain syndrome [10], have adopted rs-fMRI to detect pathophysiological changes in certain brain regions that are related to the recognition and processing of pain signals. In recent years, there has been growing interest in the use of MRI to detect the correlation between brain activities and inflammatory visceral pain in inflammatory bowel diseases (IBD) [1-3, 6, 20, 47].…”
Section: Introductionmentioning
confidence: 99%